Canadian use of aircraft for plant protection - Estey, Ralph (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ), 2004)
AbstractSince 1912, Canadians have used aircraft as aids in the protection of field crops, orchards, and forests from the ravages of fungi, insects, frost, and fire. At first, only fixed-wing aircraft could be used, but from 1947 both fixed-wing and rotary-wing aircraft have been employed. This review also relates the involvement of pioneering people and companies that have developed aerial control methods against biotic and abiotic agents damaging to our plants.